Artificial Intelligence in Management Problems - Voronin, A.; Savchenko, A. (Проблеми керування та інформатики, 2024)
The problems of optimization of a controlled object pursuing several goals are considered. A model of multi-criteria optimization has been obtained, which allows the controlled object to realize all the goals set in the entire range of possible situations without the direct participation of a person. A systematic approach to the problem of vector optimization made it possible to combine models of individual trade-off schemes into a single integral structure that adapts to the situation of making a multi-criteria decision. The advantage of the concept of a nonlinear trade-off scheme is the possibility of making a multi-criteria decision formally, which is a hallmark of artificial intelligence. Розглянуто проблеми оптимізації об'єкта управління, що переслідує декілька цілей. Отримано модель багатокритеріальної оптимізації, яка дозволяє об'єкту управління реалізувати всі поставлені цілі у всьому діапазоні можливих ситуацій без безпосередньої участі людини. Системний підхід до проблеми векторної оптимізації дозволив об'єднати моделі окремих компромісних схем в єдину цілісну структуру, що адаптується до ситуації прийняття багатокритеріального рішення. Перевагою концепції нелінійної компромісної схеми є можливість формального прийняття багатокритеріального рішення, що є відмінною рисою штучного інтелекту.